Nexus learning advanced at university and at work - CGIAR Initiative on NEXUS Gains (CGIAR System Organization, 2024)
Bringing sectors together across the WEFE nexus requires a broad foundation of nexus knowledge and capacity. NEXUS Gains and its partners launched courses, training, and open-access learning resources for students, practitioners, and leaders in Nepal and other countries. These strengthened the capacities of current and future nexus leaders, and solidified cross-sector networks for effective nexus practice and policy. One course has been institutionalized into postgraduate university programs, while another forms part of a major global learning platform.